The Role of Media in Amplifying G20 Indonesia Presidency Issues on 14 Online Media - B Arnold Simangunsong; Christy, Matahari; Reinaldi, Kevin (UPT Publikasi Ilmiah UNISBA, 2023)
On October 31, 2021, Indonesia was appointed to assume the G20 Presidency and proposed 3 (three) priority issues in the G20 Presidency, namely Digital Transformation Issues, Global Health Architecture Issues, and Sustainable Energy Issues. To obtain the success of the G20 Presidency, the role of mass media is an important factor to support this success. Using quantitative content analysis and thematic analysis units, this article seeks to obtain an overview of the role of the media on two important issues focused on at the G20 event, namely Priority Issues and Working Group Issues. The results of the study found that Kompas.com conveyed the most information about the G20 with 202 articles and issues regarding Digital Transformation were the most discussed Priority Issues. It can be concluded that the role of the media is still limited in conveying information about the G20, so it is expected to amplify the G20 through other social media and convey messages that have proximity to the audience.